Hyperin protects against cisplatin-induced liver injury in mice - Niu,Chengwei (2017)
Abstract Purpose: To evaluate the effect of hyperin in cisplatin-induced liver injury in mice. Methods: Mice were pretreated with hyperin at doses of 25 mg/kg and 50 mg/kg, respectively, for six days, and intraperitoneal injection of cisplatin (40 mg/kg) was administrated one hour after the final intragastrication of hyperin. Twenty-four hours later, blood and liver were collected for further research. Results: A single injection of cisplatin (40 mg/kg) for 24 h significantly increased serum alanine and aspartate aminotransferases (ALT/AST) and gamma glutamyl transferase (GGT) activities, whileas hyperin reversed cisplatin-induced such increases. Liver histopathological examination further demonstrated the protection of hyperin against cisplatin-induced liver injury. Further results showed hyperin reversed cisplatin-induced the increase in content of malondialdehyde (MDA) and the decrease in level of total antioxidant capacity (T-AOC) in liver. Moreover, hyperin increased the levels of superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), glutathione peroxidase (GPx), glutathione-s transferase (GST) in cisplatin-induced liver. Conclusion: Hyperin inhibits cisplatin-induced hepatic oxidative stress, which contributes greatly to the amelioration of cisplatin-induced liver injury in mice.